Fabrication and characterization of biodegradable films from sawdust - Nor Hafiza, Hamidon (2009)
This report shows the performance of the composite biodegradable film using chitosan as a primary material with addition sawdust fiber and starch as polymer matrix. The main objective of this research is to fabricate the composite biodegradable film using chitosan with sawdust fiber (CS) and the composite biodegradable film using chitosan, starch and sawdust fiber (CSS). The films were prepared by wet casting of the aqueous solution containing chitosan as the main polymer, acetic acid 1% v/v as solvent, PEG 400 as plasticizer. Sawdust was used as fiber and starch as matrix polymer were added in the chitosan solutions. The solutions were poured on a glass plate and dry it in ambient temperature. The films morphology structure was observed using Atomic Force Microscopy (AFM). The results revealed that the CS film more smooth and good integrity structure. Chemical composition of the films was investigated using Fourier Transform Infrared (FTIR) and revealed the starch presence in CSS film. The thermal properties characterization using Thermal Gravimetric Analyzer (TGA) and Differential Scanning Calorimetric (DSC) showed that thermal properties for both films are not quite different in melting and degradation temperature.